Austrocedrus chilensis: spatial association between healthy and dead trees - Rosso, Pablo H.; Havrylenko, María; Fontenla, Sonia B. (Bosque (Valdivia), 1989)
To determine the spatial arrangement of diseased trees in cypres’ forests, four plots were studied in the Parque y Reserve Nacional Nahuel Huapi (Argentina). Pielou’s test for measuring spatial segregation between two species was applied. Healthy trees were considered as members of one species and diseased trees as members of the other. Results showed that spatial segregation between them exists, suggesting that the mortality tends to occur patchily as in the case of root infections. Advantages and disadvantages of the method are discussed.